Holland egyetemek hatása a 17-18. századi magyar orvoslás kultúrtörténetében - Bozzay, Réka (Gerundium, 2015)
INFLUENCE OF DUTCH UNIVERSITIES ON THE CULTURAL HISTORY OF MEDICINE IN THE 17TH AND 18TH CENTURIES. 97 students are known who were registered as a student of medicine at Dutch universities in the Early Modern Age. he basic subjects of medical training, botany and anatomy, were met by the universities and clinical education was also introduced. Hungarian students disputed and defended doctoral theses in the Netherlands under inluence of the newest philosophical and medical theories. After having inished their medical training abroad, they became doctors of towns and provinces in their home country. Some of them continued writing scientiic works or translated works of famous European doctors. he work of the most inluential Dutch medical doctor, Hermann Boerhaave was continued by his students in Vienna and Hungary, too. His name also appeared in literary works of the 18th century.